Bitemporal Pseudohemianopia Related to the “Tilted Disk” Syndrome: CT, MR, and Fundoscopic Findings - Manfrè, Luigi; Vero, Sergio; Focarelli-Barone, Cesare; Lagalla, Roberto (American Journal of Neuroradiology, 1999)
Summary: We describe a case of the “tilted-disk” syndrome in a patient with a bitemporal field depression (a pseudohemianopia). CT and MR imaging showed thinning and prolapse of the nasal sectors of the posterior walls of the globes and flattening of the temporal portion of the globes.